Pengaruh Profitabilitas, Leverage, Pertumbuhan Penjualan dan Rapat Dewan Direksi Terhadap Manajemen Laba - Thowiyatun Nadziroh; Kartika Hendra Titisari; Suhendro (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Earnings management is an approach applied by management to influence the profit figures reported by the company, by choosing certain accounting methods or taking special steps. The results of these actions influence stakeholders in making economic decisions. Testing and analysis in this research uses the variables profitability, leverage, sales growth and board of directors meetings on earnings management. This research uses a purposive sampling method to select samples that comply with predetermined criteria. This research used 192 samples consisting of 32 companies in the primary consumer goods sector listed on the Indonesia Stock Exchange, with a research period from 2018 to 2023. This research uses secondary data taken from financial reports. The analytical method applied is multiple linear regression. The research results show that sales growth has an influence on earnings management. Meanwhile, profitability, leverage and board of directors meetings have no effect on earnings management.